Three-dimensional stress In vitro promotes the proliferation and differentiation of periodontal ligament stem cells implanted by bioactive glass - Wang, T; Li, G; Chen, J; Lin, Z; Qin, H; Ji, J (Cellular and Molecular Biology, 2016)
To analyze the biological and mechanical microenvironment on the directional differentiation of periodontal ligament stem cells (PDLSCs) In vitro. PDLSCs were cultured in three-dimensional stress system In vitro for 1, 2 and 3 weeks. Methods like immunohistochemistry and flow cytometry were adopted and the proliferation and differentiation situation of PDLSCs were determined. Bioactive glass (BAG) of 0%, 10%, 20%, 30% and 40% was implanted into PDLSCs with or without three-dimensional stress for 3 weeks, respectively. The proliferation and differentiation situation of PDLSCs were determined. The mRNA levels of Alkaline phosphatase (ALP), Type I Collagen (COL I), Type II Collagen (COL II), Bone sialoprotein (BSP), Osteocalcin (OCN) and Osteopontin (OPN) were determined by semi-quantitative RT-PCR. 30% BAG and three-dimensional stress for 3 weeks promoted the proliferation and differentiation of PDLSCs mostly. PDLSCs induced by BAG and 3D force and the control all expressed the mRNA of ALP, COLâ… and COL II. The BAG and three-dimensional stress induced PDLSCs also expressed the mRNA of BSP, OCN and OPN. BAG and three-dimensional stress indicated microenvironment In vitro can promote the proliferation and differentiation of PDLSCs.